Readmission rates and risk factors associated with emergency surgeries - Siddiqui, Mohammad S.; Albawardi, Abdulkarim A.; Alqahtani, Meshari S.; Almarshadi, Jamal A.; Alanazi, Thamer A.; Alshammari, Fahad H.; Almalki, Marwan T.; Mohamed, Dalal A.; Alamoudi, Osama O.; Almalky, Ayman J.; Alobaidi, Ahmed E. (International Journal Of Community Medicine And Public Health, 2022)
Emergency surgery requires complex and diversified skills and talents to execute procedures from several fields of surgery within 24 hours. The prevalence of emergency surgery is also increasing in recent times and the cohort for emergency general surgery is particularly at risk for readmission. Readmission is considered as one of the predictors of the quality of healthcare. Readmission following emergency surgery is frequent and varies greatly based on patient characteristics and diagnostic types. Readmission is associated with the significant morbidity and mortality, also adds to the increased hospital burden. Various risk factors account for the readmission. The purpose of this research is to review the available information about the readmission rates and risk factors associated with emergency surgeries. About half of patients undergoing emergency surgeries will experience a postoperative complication, and postoperative complications have a strong correlation with hospital readmission. Postoperative complications and readmission have a significant negative influence on patient quality of life and healthcare resources. Different studies have reported an increased prevalence of readmissions after emergency surgeries. Surgical site infection, increased length of hospital stays, readmission at the non-index hospital, comorbidities are some of the commonly reported risk factors of readmission. Establishment and implementation of the preventive strategies for the control of risk factors of readmission can help in reducing the readmission burden.